Effect of Procedural Justice in Spouse Assault in Milwaukee, Wisconsin, 1987-1989 - Paternoster, Raymond ([Verlag nicht ermittelbar], 2008)
The purpose of the research project was to examine the extent to which the perception of procedural fairness by suspects arrested for spouse assault effectively inhibited their subsequent violence. The data for this study were collected for the MILWAUKEE DOMESTIC VIOLENCE EXPERIMENT, 1987-1989 (ICPSR 9966), which was conducted from April 1987 to August 1988. In this experiment, all cases of misdemeanor domestic battery where probable cause to arrest existed were randomly assigned to one of three conditions: (1) warning with no arrest, (2) arrest with a brief detention period (average of 3 hours), and (3) arrest with a longer detention period (average of 11 hours). Variables include demographic and background information, as well as descriptive variables pertaining to the domestic violence incident.